2012
DOI: 10.1186/2046-9063-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, species composition of microzooplankton from the coastal waters of Port Blair, South Andaman Island

Abstract: BackgroundMicrozooplankton consisting of protists and metazoa <200 μm. It displays unique feeding mechanisms and behaviours that allow them to graze cells up to five times their own volume. They can grow at rates which equal or exceed prey growth and can serve as a viable food source for metazoans. Moreover, they are individually inconspicuous, their recognition as significant consumers of oceanic primary production. The microzooplankton can be the dominant consumers of phytoplankton production in both oligo- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…followed by an inability of MZP to graze on this larger phytoplankton. A similar observation was recorded during a diatom bloom in the East China Sea and Andaman Coastal waters (Elangovan et al, ; Lee & Kim, ). In earlier studies, the phytoplankton composition from the same region is well reported with the chain‐forming species such as Chaetoceros sp., Thalassiosira sp., Rhizosolenia sp., and Bacillaria sp.…”
Section: Discussionsupporting
confidence: 85%
“…followed by an inability of MZP to graze on this larger phytoplankton. A similar observation was recorded during a diatom bloom in the East China Sea and Andaman Coastal waters (Elangovan et al, ; Lee & Kim, ). In earlier studies, the phytoplankton composition from the same region is well reported with the chain‐forming species such as Chaetoceros sp., Thalassiosira sp., Rhizosolenia sp., and Bacillaria sp.…”
Section: Discussionsupporting
confidence: 85%
“…Junglighat (92° 43'56"N and 11° 39'21"E) is a moderately polluted area found in the East Coast of Andaman [15] with a sewage influx in the centre of the area. Junglighat Bay is situated near Haddo harbour and is a major fish landing centre for Port Blair.…”
Section: Materials and Methods 1) Description Of The Study Areamentioning
confidence: 99%
“…The triplicate surface water samples were collected in clean polyethylene bottles for analysis of nutrients, which were stored immediately in an ice box before transfer to the laboratory. The collected water samples were filtered by using a Millipore filtering system and then analyzed for dissolved inorganic nitrate, nitrite, reactive silicate and inorganic phosphate, adopting the standard procedures described by [15] and expressed in µmol L -1 . For the identification of species, 1 ml of sample were put on a Sedgwick rafter counter slide, covered with a cover glass and examined under light microscope.…”
Section: ) Sample Collection and Analysismentioning
confidence: 99%
“…Despite the importance of superoxide to the growth and activity of Trichodesmium, the conditions promoting extracellular production are largely unknown and unexplored in oligotrophic environments. Further, Trichodesmium blooms oftentimes also contain high abundances of other plankton, including, for instance, the widespread diatom Coscinodiscus (Karthik et al 2012), that may contribute to ROS cycling within the bloom community. Accordingly, the goals of this study were to measure rates of superoxide production by natural Trichodesmium populations and associated diatoms obtained from various surface waters in the Sargasso Sea and to evaluate how these activities were modulated.…”
mentioning
confidence: 99%